*Ø§Ø³ØªÙ†Ø¨Ø§Ø· Ø¹Ù„Ø§Ù‚Ø© Ø´Ø¨Ù‡ ØªØ¬Ø±ÙŠØ¨ÙŠØ© Ù„ØØ³Ø§Ø¨ Ù‚Ø¯Ø±Ø© Ø§Ù„Ø¥ÙŠÙ‚Ø§Ù Ø§Ù„Ø§Ù„ÙƒØªØ±ÙˆÙ†ÙŠØ© Ù„Ù…Ø¨Ø±ÙˆØªÙˆÙ†Ø§Øª ÙˆØ¬Ø³ÙŠÙ…Ø§Øª Ø£Ù„ÙØ§ Ø§Ù„Ù…ØªÙØ§Ø¹Ù…Ø© Ù…Ø¹ Ø¨Ø¹Ø¶ Ø§Ù„Ù…Ø±ÙƒØ¨Ø§Øª Ø§Ù„Ø¹Ø¶ÙˆÙŠØ© - Aweed Kadhim, Asst. Prof. Rashid; Abdul Sada Kadhim, Shahla (Al-Qadisiyah Journal of Pure Science, 2017)
In this research find semi-empirical relationship to calculate the electronic stopping power of charged (protons & alpha particles) interacting with organic compounds : - [Polypropylene (C3H6), Polycarbonate (C16H14O3), Mylar (C10H8O4), Polyvinylalcohol (C2H4O), Polyoxymethylene (CH2O), Polyacrylonitrile (C3H3N), Polyvinylpyrrolidone (C6 H9 NO), Polyvinylacetate (C4H6O2), Kapton (C22 H10 N2 O5) , Bakelite (C44 H36 O6)] using the ratio âŒ© âŒª, within range of energy [0.01-1000] MeV, and by comparing the obtained results with the results of the SRIM 2012 program for the same projectiles in these compounds have shown good agreement with the results of the SRIM 2012.